STYLISTIC FEATURES OF SUBTITLE AND DUBBING TEXTS IN THE ENGLISH LANGUAGE - Bozorova Vasila Ilkhomovna (International Journal of Literature and Language Studies, 2026)
This article examines the specialized linguistic, syntactic, and pragmatic features of subtitle and dubbing texts within English audiovisual discourse. Operating within a poly-semiotic and multimodal screen environment, audiovisual translation (AVT) acts as a dynamic system where verbal paths must continuously balance artistic intent against strict technical and cognitive constraints. Through a comparative structural analysis, this study maps the core differences between the visual, cross-modal shift of subtitling and the oral, iso-modal replacement of dubbing. The findings reveal that subtitling relies on intense lexical density updates, syntactic simplification, and the systematic removal of conversational discourse markers (pragmatic pruning) to respect spatial boundaries (35–42 characters per line) and temporal guidelines. Conversely, dubbing focuses on phonetic harmony, mouth shape alignment (lip-sync), and matching the exact timing of breath tracks (isochrony) to maintain natural dialogue cadence and physical realism. Additionally, this article evaluates the ongoing tension between spoken socio-dialectal speech variations and the standardization rules of written screen text. Ultimately, the paper demonstrates that English screen texts are never static, word-for-word copies of spoken dialogue; instead, they are highly specialized communicative frameworks engineered to manage visual cognitive load while fully preserving narrative depth and cinematic immersion.